Efeitos da prática autocontrolada e da percepção de relacionamento social na aprendizagem de uma tarefa motora aquática - Gonzalez, Daniela Hollweg (2012)
This study investigated the effects of both self-controlled practice and the giving of information that induces a perceived affection (relatedness) on aquatic motor skill learning. Forty recreational swimmers of both sexes participated. They performed a swimming task at different intensities. The swimmers wee divided into four groups. Two groups received a self-controlled knowledge of results (KR), one having a positive feeling of relatedness (SKP) and the other a neutral feeling of relatedness (SKN). The other two groups received an equivalent KR, one having a positive feeling of relatedness (EKP) and the other a neutral feeling of relatedness (EKN). The varied perception of relatedness was also manipulated in the groups. Through the analysis of the data with ANOVA, using the statistical package SPSS, it was concluded that the SKP group obtained better results in all the phases.